Coinjection of C6, C7, and CO2 with steam to improve low-pressure SAGD process. (15th February 2019) - Zare, Alireza; Hamouda, Aly A.
Highlights: Combined C6 and CO2 solvents coinjection with steam improved oil recovery. Higher oil recovery is linked more to solvent properties than steam chamber shape. Solubility of C6 and C7, and CO2 diffusion into the oil enhanced recovery. The coinjection process resulted in a less fluctuated subcool temperature. Abstract: Steam assisted gravity drainage (SAGD) is one of the most widely used processes of thermal recovery for heavy oil. Investigating the effectiveness of solvent coinjection with steam is an important aspect in the optimisation of SAGD process. So far, however, the effects of using CO2 have not been closely examined. This study sheds light on the addition of hydrocarbon solvents with CO2 which reached earlier maximum ultimate oil recovery (90%) than that for other solvents coinjection. This study shows that solubility of C6, heat loss reduction and CO2 diffusion, are the main recovery mechanism in enhancing oil recovery. The present study highlights the steam propagation in the presence of C6 and CO2 and its relation to enhancing oil recovery. It is interesting to observe that physical properties of the injected fluid reduce the energy consumption. Another finding is that solvent coinjection leads to stable subcool, hence increase oil recovery.